IMPLEMENTASI PERENCANAAN PEMBANGUNAN TAHUN 2015 DI KOTA KEDIRI BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 54 TAHUN 2010 - Novita Susilowati (Universitas Islam Kadiri, 2019)
The purpose of this research include: (1) To know how the process of Development Planning of Kediri City in 2015 based on Peraturan Menteri Dalam Negeri Nomor 54 Tahun 2010. (2) Consistency between plans and implementation of the budget of Kediri city in 2015 . (3) to know the strategies of local Government in control and evaluation of the Development Planning of Kediri city in 2015. This research used qualitative method that emphasizes the process of research than it result, so it is not the absolute thruth is sought, but deep understanding of something that is researches. Discriptivelly, it will discribe an object of the reseach deeper namely the implementation of development planning Kediri City in 2015 based on Peraturan Menteri Dalam Negeri Nomor 54 Tahun 2010. This results of the research showed that a lot of complexity of the problems in preparation of planning documents, with the result of the consistency between the work plan document and a low budget execution documents implementation do not necessarily indicate poor planning but there are things that underlie to take the policy in the administrative process, financial management and accountablility and public transparency. Governmet of Kediri City in the planning process has been carrying out the stages procedures, control and evaluation in accordance with the regulation of Peraturan Menteri Dalam Negeri Nomor 54 Tahun 2010